1-Ferrocenylbutane-1, 3-dione as a scaffold for ferrocenyl-based ligands: Synthesis, X-ray and computational studies. (1st April 2020) - Alia, Joseph; Carpenter, Nancy E.; Albrecht, Amanda J.; Alexander, Sharon; Bullick, Taylir L.; Helmin, Andrew J.; Hubers, Scott A.; Janzen, Daron E.; Koehn, Jordan T.; Nyland, Bethany; Thoma, Laura; Weyer, Lynn; et al.
Graphical abstract: Abstract: Advanced precursors to novel ferrocene-based ligands Cp2 FeC(O)CH(R)C(O)CH3 (R = benzyl, allyl) were synthesized from 1-ferrocenylbutane-1, 3-dione via active methylene chemistry. Crystal structures were obtained and computational studies carried out to explore the structural features of these new compounds. Addition of carbonyl electrophiles resulted in the formation of unexpected products, which were identified and mechanisms for their formation proposed.